Haematopoietic stem cell survival and transplantation efficacy is limited by the BH3‐only proteins Bim and Bmf. Issue 1 (24th November 2012) - Labi, Verena; Bertele, Daniela; Woess, Claudia; Tischner, Denise; Bock, Florian J.; Schwemmers, Sven; Pahl, Heike L.; Geley, Stephan; Kunze, Mirjam; Niemeyer, Charlotte M.; Villunger, Andreas; Erlacher, Miriam
Abstract: Anti‐apoptotic Bcl‐2 family members are critical for the regulation of haematopoietic stem and progenitor cell (HSPC) survival. Little is known about the role of their pro‐apoptotic antagonists, i.e. 'BH3‐only' proteins, in this cell compartment. Based on the analysis of cytokine deprivation‐induced changes in mRNA expression levels of Bcl‐2 family proteins, we determined the consequences of BH3‐only protein depletion on HSPC survival in culture and, for selected candidates, on engraftment in vivo . Thereby, we revealed a critical role for Bim and Bmf as regulators of HSPC dynamics both during early engraftment and long‐term reconstitution. HSPCs derived from wild‐type donors were readily displaced by Bim‐ or Bmf‐deficient or Bcl‐2‐overexpressing HSPCs as early as 10 days after engraftment. Moreover, in the absence of Bim, significantly lower numbers of transplanted HSPCs were able to fully engraft radio‐depleted recipients. Finally, we provide proof of principle that RNAi‐based reduction of BIM or BMF, or overexpression of BCL‐2 in human CD34 + cord blood cells may be an attractive therapeutic option to increase stem cell survival and transplantation efficacy. Abstract : Many haematological diseases can only be cured by blood stem cell transplantation. The authors show that apoptosis inhibition at the level of Bcl‐2 proteins leads to an extended life span of blood stem cells and facilitates engraftment in vivo.